2011
DOI: 10.1007/s11214-010-9708-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Solar Radio and Hard X-ray Emission

Abstract: This review discusses the complementary relationship between radio and hard X-ray observations of the Sun using primarily results from the era of the Reuven Ramaty High Energy Solar Spectroscopic Imager satellite. A primary focus of joint radio and hard X-ray studies of solar flares uses observations of nonthermal gyrosynchrotron emission at radio wavelengths and bremsstrahlung hard X-rays to study the properties of electrons accelerated in the main flare site, since it is well established that these two emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 110 publications
10
115
0
Order By: Relevance
“…We have mentioned that a similar flattening was reported earlier based on the microwave-to-X-ray slope comparisons (Silva et al 2000;White et al 2011). In the previous cases, however, the radio-derived and X-ray-derived spectral indices of nonthermal electrons were obtained using one or another approximation, e.g., from the thick-target fit of the footpoint X-ray emission or a simplified analytical Dulk-Marsh formula for the GS spectrum, which necessarily involves some level of Figure 2); (e): [30,50,70,90]% contours of the OVSA 5.6 GHz emission (white; same as in Figure 2) on top of the computed microwave 5.6 GHz image; (f): model HXR emission at 15 keV (blue) on top of the model microwave image at 5.6 GHz.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We have mentioned that a similar flattening was reported earlier based on the microwave-to-X-ray slope comparisons (Silva et al 2000;White et al 2011). In the previous cases, however, the radio-derived and X-ray-derived spectral indices of nonthermal electrons were obtained using one or another approximation, e.g., from the thick-target fit of the footpoint X-ray emission or a simplified analytical Dulk-Marsh formula for the GS spectrum, which necessarily involves some level of Figure 2); (e): [30,50,70,90]% contours of the OVSA 5.6 GHz emission (white; same as in Figure 2) on top of the computed microwave 5.6 GHz image; (f): model HXR emission at 15 keV (blue) on top of the model microwave image at 5.6 GHz.…”
Section: Discussionsupporting
confidence: 88%
“…However, we quickly find that it is not possible to obtain a good fit to the microwave spectrum with such a steep electron energy spectrum, irrespective of other model assumptions. Unavoidably, we have to assume the existence of a spectral break up above some energy, to a lower spectral index of about δ n2 ≈3.5 to fit the high-frequency microwave spectral slope, which may not be surprising given that a number of previous radio-to-X-ray comparisons (see, e.g., Silva et al 2000;White et al 2011, and references therein) concluded that the radio-derived spectra of the nonthermal electrons are often flatter than the X-rayderived ones.…”
Section: D Modeling: the Rise Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The measured value is in the bounds of the estimates δ MW = γ X + 1.5 and δ MW = γ X − 0.5 for the radio-emitting electrons depending upon whether we assume thick target or thin-target approximation for the X-ray source (e.g. White, Benz, and Christe, 2011).…”
Section: The Microwave Sourcesmentioning
confidence: 91%
“…The impulsive radio and X-ray emissions are produced by energetic electrons via the gyro-synchrotron and bremsstrahlung processes, respectively White et al 2011). The eastern source is partially self-absorbed at 17 GHz, which means that the 17 GHz flux density of the impulsive emission component derived in the previous section should be treated as a lower limit for gyro-synchrotron emission since the 34 GHz flux density of the eastern source (which is subtracted from the 17 GHz flux density) is slightly higher than that at 17 GHz.…”
Section: Spectral Analysesmentioning
confidence: 99%